Pengaruh eco-efficiency, environmental performance dan good corporate governance terhadap firm value: Studi empiris - Pratama, Ade Setia; Ainiyah, Asmarita Khurrotil (Implementasi Manajemen & Kewirausahaan, 2023)
A company that wants to maintain its existence must be able to increase the value of the company. There are several factors that can affect company value, including stakeholder perceptions of the efficient use of raw materials, environmental performance and good corporate governance so that later this will increase trust both in the present and in the future. The purpose of this study is to determine whether there is a significant effect of the three independent variables on the overall firm value. The approach used in this research is quantitative. The data collection instrument was carried out by collecting data on the website of the Indonesia Stock Exchange during the 2017-2022 reporting period. The samples used were 39 Real Estate companies listed on the Indonesia Stock Exchange and data analysis used multiple linear regression. The result of this study is that environmental performance is not proven to significantly affect company value. However, two other variables, namely economic efficiency and corporate governance, proved to have a significant effect. This is because the two variables have a dominant effect and the output can be directly felt by the company's stakeholders.